Self-Knowledge and The Advaitic Liberation - Tiwari, Kapil N. (Journal of Dharma, 1977)
The present paper confines itself to the understanding of self- knowledge and its implications for the Advaitic concept of liberation according to Samkara. This study seems important to me in order to examine the question of self-knowledge in all its mean- ings in a way that makes it central to the general problem of existence rather than something outside and exclusive of it. Also this kind of study leads us to another very plausible hypothesis which can be shared by all great religions of India that self-knowledge is neither a pure intellectualism nor a simple moralism and therefore to understand it in the ordinary logical and ethical sense will be a grave injustice to the spirit of these religions. In other words, the value and validity of experience of any type can be legitimately accepted within the general framework of self-knowledge so far as they seek to interpret and help the religious goal of life but they cannot be regarded as substitutes for it.